Australian nursing and midwifery educators delivering evidence-based education in Tanzania: A qualitative study - Gower, Shelley; van den Akker, Jose; Jones, M.; Dantas, Jaya; Duggan, Ravani (Churchill Livingstone, 2016)
Since 2011, Western Australian nursing and midwifery educators have been providing evidence-based continuing education to Tanzanian health professionals. Despite thorough preparation before departure, differences in local resource levels and available facilities have necessitated impromptu adaptation of curriculum content and delivery methods to ensure an effective program was delivered. This study explored the personal, cultural and teaching strategies utilised by Western Australian nursing and midwifery educators in Tanzania and examined if the transferability of education packages was influenced by the educators' cultural competence. Using a qualitative exploratory approach, data was collected from 15 Western Australian nursing and midwifery educators using a demographic survey and in-depth individual semi-structured interviews. The core themes identified from the analysis were Determination to learn, Assessing needs, Communication skills and Greater understanding. These findings are described using the conceptual framework of Campinha-Bacote's The Process of Cultural Competence in the Delivery of Healthcare Services. With appropriate levels of cultural competence, international health professionals can be effective at providing ongoing professional development to colleagues in developing country contexts, which may help address difficulties with retention and motivation of staff. It is essential that prior to departure cultural competence training is provided to educators to enhance their teaching capacity and effectiveness in international settings.